Play Therapy to Reduce Traumatic Stress in Earthquake-affected Children in North Lombok, West Nusa Tenggara - Lis Triasari; Ah. Yusuf; Sestu Retno D. A; Triyana P.D; Zaenal Abidin (International Journal of Nursing and Health Services (IJNHS), 2020)
Intruduction: Play therapy is a therapy that is appropriate to the level of child development as a period of play after exposure to a disaster. Children are the group most vulnerable to traumatic stress due to exposure to disasters. Children are the group most vulnerable to traumatic stress due to exposure to disasters. As a result, children will experience physical and psychological trauma (psychosocial) because they may lose their parents or family or even witness the closest people themselves to be injured and so on. The use of play therapy is based on understanding the development of children regarding the importance of playing with children's lives because through games, children can express their emotions and thoughts through the universal language without relying on verbalization. Methods: The research design used was quasi-Experimental with a non-randomized control group pre-post-test design design. The population in this study was elementary school children who attended school in the North Lombok Regency. The sample used was 90 students in accordance with the inclusion criteria and divided into two groups, namely the treatment group with 45 students and the control group with 45 students. Sampling was done by Multistage Random Sampling then continued with Simple Random Sampling Data obtained from questionnaires were analyzed using the Independent test t Test and Paired t test with a significance level of 0.05. Result: The statistical results using the Paired t test showed that there was an effect of play therapy on influence of therapy playing against traumatic stress in the intervention group (p = 0,000). Conclusion: Play therapy can help reduce traumatic stress in children. The effectiveness of play therapy is because children are more able to communicate through games. Play therapy carried out in the school environment is more effective because the school is the second environment after the family. Schools can be a place for children to express their feelings by sharing stories with peers who they think have the same feelings they experience. Recommendation: Further treatment is needed to evaluate symptoms of stress in children after exposure to a disaster. Keywords: Children, traumatic stress, natural disasters